X-Ray Diffraction Analysis of Bitumen Containing Untreated and Treated Waste Cooking Oil - Wan Nur Aifa, W. A.; Putra Jaya, Ramadhansyah; Mohd Rosli, Hainin; Mohd Rosli, Mohd Hasan; Ekarizan, Shaffie (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Abundant of waste cooking oil (WCO) production can cause prominent adverse impact and threat to the environment if not properly managed and disposed. Therefore, recycling or reusing WCO in modified asphalt binder is considered as an effective utilisation and environmental benefits. Hence, this study was to evaluate the chemical characteristic of untreated and treated WCO in modified binder through X-Ray diffraction analysis. The results indicated that the amorphous structure was present in the control and modified binders with untreated and treated WCO. The flat trends tabulated in XRD graph for modified binder depicted the uniform dispersion and homogeneous solution,was achieved between the untreated and treated WCO with the asphalt binder during mixing process.